281 Collateral Damage: The Cost of Failing to Take a Comprehensive Collateral History for Older Adults with Cognitive Impairment. (16th September 2019) - Doyle, Kate; Fitzpatrick, Donal; Finn, Gerard; Gallagher, Paul
Abstract: Background: Age-related syndromes of cognitive impairment, including delirium and dementia, are becoming more prevalent in our hospitals. Patients with cognitive impairment are often unable to provide information relating to their pre-morbid cognition and function as well as their admission diagnosis. Such information is essential to correctly identifying delirium and dementia, as well as making an accurate diagnosis and planning appropriate treatment. It is the standard of care recommended by both the Irish National Audit of Dementia 2014 and the UK National Audit of Dementia Care 2017 that a collateral history is obtained. Methods: We reviewed the medical notes and conducted brief structured interviews with nursing staff for 100 medical inpatients aged ≥75. Results: Only 44% of patients with cognitive impairment had a collateral history. Half of patients described as having dementia did not have any further detail on the severity of dementia documented. 80% of collateral histories were sourced by the admitting NCHD; if the collateral history was not obtained on admission, it was unlikely to be obtained at all. Among those for whom a collateral history was obtained, the level of detail regarding pre-morbid cognition, function, mobility and continence was sparse. The most common informant was the patient's son or daughter (66%), followed by spouse (16%). Only 13% of patients had formal cognitive testing. Conclusion: Acute illness characteristically causes significant impairments in cognition and function in frail older patients. Identifying and reversing these impairments is impossible without a comprehensive collateral history. It is alarming that such an essential component of clinical assessment is so often disregarded and highlights the lack of awareness from clinicians of the importance of collateral history in the management of patients with dementia and delirium. This must be emphasised in both undergraduate and postgraduate teaching. An appropriate admission proforma would also promote competent collateral history taking.